1928
DOI: 10.1017/s0022172400009530
|View full text |Cite
|
Sign up to set email alerts
|

A Study of Non-specific Complement-fixation with particular reference to the Interaction of Normal Serum and certain Non-antigenic substances

Abstract: 1. When a solution of commercial peptone is substituted for antigen in a complement-fixation test with the unheated normal serum of certain species (man, ox, sheep, horse, rabbit, white rat), a definite fixation reaction occurs both at 37° C. and at 0° C. In the ox, sheep, horse and rabbit this property of serum is partially stable at 55° C., but normal human serum and the serum of the white rat are inactive after heating at this temperature. The property is resident mainly in the carbonic-acid-insoluble globu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
11
0

Year Published

1930
1930
2005
2005

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 10 publications
0
11
0
Order By: Relevance
“…The substance present in the antigen responsible for this reaction can be sedimented at 20,000 r.p.m. (Kidd and Friedewald, 1942) and the antibody-like substance in the serum can be destroyed by heat (Casals and Palacios, 1941;Mackie and Finkelstein, 1928). At the same time antisera should be prepared by inoculation of animals with homologous tissue to prevent the formation of antibody to that particular tissue.…”
Section: Results Of Complement Fixadonmentioning
confidence: 99%
“…The substance present in the antigen responsible for this reaction can be sedimented at 20,000 r.p.m. (Kidd and Friedewald, 1942) and the antibody-like substance in the serum can be destroyed by heat (Casals and Palacios, 1941;Mackie and Finkelstein, 1928). At the same time antisera should be prepared by inoculation of animals with homologous tissue to prevent the formation of antibody to that particular tissue.…”
Section: Results Of Complement Fixadonmentioning
confidence: 99%
“…Eastwood (1920), in a review of early experimental work on the nature of the Wassermann reaction, showed how much of this was based on the opinion (which it appeared to support) that the syphilitic reagin was not an antibody arising de novo, but a constituent of normal plasma which was physically altered in syphilis and thereby changed from a previously masked state. Mackie and Watson (1926) and Mackie and Finkelstein (1928) showed that the Wassermann reagin was a serum constituent which could be found in heat-sensitive form, being destroyed at 55°C. in many, if not all, normal human sera, but was characteristically heat-stable at 550 C. in the sera of rabbits and certain other animals.…”
Section: Discussionmentioning
confidence: 99%
“…The general system adopted for estimating complement-fixation quantitatively was that previously described (Mackie and Finkelstein, 1928).…”
Section: Methodsmentioning
confidence: 99%
“…IN a previous communication the authors drew attention to the occurrence of complement-fixation by normal serum along with various non-antigenic substances, and recorded the results of a study of this phenomenon with particular reference to the serum principle or principles concerned in the reaction (Mackie and Finkelstein, 1928). Though no conclusive interpretation of the results could be offered, a close analogy was established between the reacting agent of the serum and a natural antibody, e.g.…”
mentioning
confidence: 99%